Tinjauan Mekanisme Pengelolaan Wakaf Uang Berbasis Digital Pada Lembaga Wakaf Majelis Ulama Indonesia Pusat - Ahmad Munandar; Asyari Hasan (ITB AAS INDONESIA Surakarta, 2023)
Talking about waqf is familiar to us both in practice and in theory. Waqf in the concept of religion has a dimension of worship, waqf is also called charity charity. The development of waqf has recently been increasingly supported by the government and MUI issued MUI Fatwa No. 2 of 2002 concerning Cash Waqf. The data used in this study are primary data obtained from direct interviews with the Central MUI Waqf Institution and the official website of the Indonesian Ulema Council and MUI Waqf Institutions. The findings of this study are that there is still no provision if direct investment in the form of investment in the MSME and agricultural sectors suffers losses, so when referring to the value of the waqf itself, the waqf may not decrease in the least from the initial nominal amount. This study also recommends the need for collaboration with financial institutions that already have applications or features that already contain waqf, such as with Bank Syariah Indonesia so that it is easier for people to make waqf transactions.